2021
DOI: 10.1680/jgeot.18.p.220
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of water retention behaviour of bentonite based on mineralogy and mercury intrusion porosimetry tests

Abstract: This paper develops a water retention model based on the soil mineralogy and microscopic features of the material behaviour. The model estimates the water content at a given total suction as the sum of the bentonite minerals interlayer water and the water in the interparticle pores. The paper proposes simple formulae to estimate the interlayer water content and interlayer void ratio based on mineralogical properties. Additionally, the model uses the mercury intrusion porosimetry measurements to approximate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…9, it can be seen that the pore size before and after shear was significantly increased due to the chemical action of the salt solution, which is consistent with the experimental results of Yu and Tian (2019); the overall pore size became smaller after experiencing the shear action. There are significant differences in the interval of microscopic porosity for different types of soils, and a large number of studies have shown that clayey soils are often categorized according to the pore scale into microscopic micropores (pores between lamellar clay particles in the range of 1.2 nm or 0.4 Å -12 Å; intra-aggregate pores in the range of 12 Å -200 nm), and macropores (inter-aggregate pores greater than 200 nm) (Abed and Sołowski. 2021;Seiphoori et al 2014).…”
Section: Aperture Distributionmentioning
confidence: 99%
“…9, it can be seen that the pore size before and after shear was significantly increased due to the chemical action of the salt solution, which is consistent with the experimental results of Yu and Tian (2019); the overall pore size became smaller after experiencing the shear action. There are significant differences in the interval of microscopic porosity for different types of soils, and a large number of studies have shown that clayey soils are often categorized according to the pore scale into microscopic micropores (pores between lamellar clay particles in the range of 1.2 nm or 0.4 Å -12 Å; intra-aggregate pores in the range of 12 Å -200 nm), and macropores (inter-aggregate pores greater than 200 nm) (Abed and Sołowski. 2021;Seiphoori et al 2014).…”
Section: Aperture Distributionmentioning
confidence: 99%
“…The understanding of microstructure evolution when the water content and the chemical concentration of salts change, is fundamental for an accurate replication of unsaturated clayey soil behaviour, as the microstructure changes directly affect macroscopic properties, such as water retention curve, see e.g. Della Vecchia et al, 2019, Abed andSołowski, 2021. As evidenced by ESEM (Environmental Scanning Electron Microscopy) and MIP (Mercury Intrusion Porosimetry) tests, compacted clay microstructure may consist of clay clusters or aggregates (see Figure 1). After preparation, soil microfabric evolves with water content, as shown by, among others, Lloret et al (2003) and Romero et al (2011) for compacted clayey soils and Monroy et al (2010) for reconstituted specimens.…”
Section: Figure 1 Schematic Representation Of Clay Microstructurementioning
confidence: 99%
“…Methods from materials science, such as scanning and transmission electron microscopy (SEM/TEM), mercury intrusion porosimetry (MIP), and wide or small angle X-ray or neutron scattering (W/SAXS, SANS) (e.g., Glatter and Kratky 1982;Toer and Reimer 1998;Giesche 2006) have been introduced in geomechanics to further probe clays at microscale despite their inherent limitations for use in fine-grained materials (Yao and Liu 2012;Deirieh et al 2018). The ultimate aim is to link the micro and macro response (e.g., Pusch 1970;Delage and Lefebvre 1984;Djéran-Maigre et al 1998;Hicher et al 2000;Ringdal et al 2010;Delage 2010;Hattab and Fleureau 2011;Hattab et al 2013;Suuronen et al 2014;Wensrich et al 2018;Birmpilis et al 2019;Cotecchia et al 2019;Delage and Tessier 2021;Abed and Sołowski 2020;Schuck et al 2020;Dor et al 2020;Zhao et al 2020). Regardless of the experimental method, either a bulk response of the complete sample volume (MIP, W/SAXS, SANS), a twodimensional (2D) map of the integrated response along the transmitted X-ray/electron beam (scanning W/SAXS and TEM), or a 2D surface profile (with a certain depth of view) is obtained (SEM).…”
Section: Introductionmentioning
confidence: 99%